The Correlation Between Parenting Styles and Socialization Skills of 4-5 Year Old Children at Sai Prema Kumara Kindergarten, Denpasar - Dian Cahyani, L. Eky Fajaria; Santika, I Putu; Wijaya, I Putu Artha; Kusuma Putra, Putu Wira (Jurnal Kesehatan, 2026)
Introduction: Socialization skills in preschool children are crucial as a foundation for preparing them for their future academic success. Parenting styles play a crucial role in character formation and socialization skills in children. This study aimed to determine the correlation between parenting styles and socialization skills of 4-5 years old children at Sai Prema Kumara Kindergarten, Denpasar. Method: This research employed a cross-sectional methodology. Purposive sampling was used to choose a sample of thirty-one people. The Chi-Square statistical test was performed to analyze the data. Results: The study’s findings revealed that the majority of parents’ parenting techniques were democratic (64.5%), while the majority of children demonstrated high socialization skills (71%). Bivariate analysis revealed a significant correlation between parenting styles and socialization skills in children aged 4-5 years at Sai Prema Kumara Kindergarten, Denpasar (p-value < 0.05). Future researchers are encouraged to investigate other variables that can give the appropriate stimulus to maximize sociability skills in preschool children. Conclusion: Based on the results of the analysis using the Chi-square statistical test between parental parenting and socialization ability in children aged 4-5 years at PAUD Sai Prema Kumara, the significance result obtained was 0.022 so that the p value < 0.05. This shows that there is a relationship between parental parenting and the socialization ability of children aged 4-5 years at PAUD Sai Prema Kumara.